Peningkatan Aktivitas dan Keterampilan Berkomunikasi Mahasiswa Dalam Mata Kuliah Konsep Dasar Sains MI dengan Model Pembelajaran Everyone Is A Teacher Here - Mutmainah Mutmainah; Rhyan Prayuddy Reksamunandar (IAIN Manado, 2023)
This research aimed to investigate the improvement of activity and communication skills of students in the MI Basic Science Concepts course at the Madrasah Ibtidaiyah Teacher Education Study Program IAIN Manado using the Everyone Is a Teacher Here learning model.The research subjects were 16 students of semester IV enrolled in the 2021/2022 - 2022/2023 academic year, consisting of 1 male and 15 female students. The instruments used were observation sheets and communication skills tests. Research data were analyzed using descriptive statistical analysis technique.The results revealed that the students' activity and communication skills from cycle I to cycle II through the Everyone Is a Teacher Here learning model were increased. In cycle I, the communication skills and activities reached an average of 54.7% and increased to 74.7% in cycle II. It means that the improvement reach 18% from cycle I. Thus, to make the students active in learning process, to express their ideas and opinions smoothly and correctly, the lecturers should train students' communication skills